Magnetization of laser-produced plasma in a chiral hollow target. (16th March 2017) - Korneev, Ph; Tikhonchuk, V; d'Humières, E
Abstract: It is demonstrated that targets with a broken rotational symmetry may facilitate the generation of a strong axial (poloidal) magnetic field. An intense laser beam irradiating such a target creates strong electron currents carrying vorticity and producing strong spontaneous magnetic fields. Combined with laser-based acceleration schemes, such targets may be used for generation and guiding of magnetized, collimated particle or plasma beams.